Efficacy and safety of Lacticaseibacillus rhamnosus R0011 and Lactobacillus helveticus R0052 as an adjuvant for Helicobacter pylori eradication: a double-blind, randomized, placebo-controlled study - Kiattiweerasak, Anya; Aumpan, Natsuda; Chonprasertsuk, Soonthorn; Pornthisarn, Bubpha; Siramolpiwat, Sith; Bhanthumkomol, Patommatat; Nunanan, Pongjarat; Issariyakulkarn, Navapan; Mahachai, Varocha; Yamaoka, Yoshio; Vilaichone, Ratha-korn (Frontiers in Gastroenterology, 2023)
Background Helicobacter pylori eradication is recommended as a way of providing symptomatic relief for dyspepsia. The limited efficacy of triple therapy is a major problem in many countries, including Thailand. Some probiotics have been shown to improve the H. pylori eradication rate and reduce side effects. This study aimed at evaluating the efficacy of probiotic (Lacidofil® STRONG) as adjuvant to standard triple therapy. Methods This randomized, double-blind, placebo-controlled study was conducted between July 2020 and June 2022. Eligible patients with H. pylori gastritis (i.e., n=90 out of the 160 patients screened) were randomized to receive 14-day standard triple therapy either with probiotics or with a placebo (N=45/group). The treatment regimen entailed 30 mg lansoprazole administered twice daily, 1,000 mg amoxicillin administered twice daily, and 1 g clarithromycin modified-release formulation administered once daily. A probiotic capsule containing Lacticaseibacillus rhamnosus R0011 and Lactobacillus helveticus R0052 (Lacidofil® STRONG) or placebo were given twice daily during the eradication therapy and for an additional 4 weeks. Successful H. pylori eradication was defined as a negative 13C-urea breath test at least 4 weeks after complete eradication. Results As per-protocol analysis, eradication rates after the 14-day regimen with probiotic or placebo were 90.9% and 75.0% (p=0.047), respectively. Antibiotic susceptibility testing demonstrated high clarithromycin resistance (24%). For clarithromycin-resistant strains, there was no statistical difference in eradication rates between the probiotic and placebo groups. Furthermore, probiotic supplementation significantly reduced treatment side effects, including bloating (OR 0.27 [95% CI 0.10 to 0.75], p=0.012), diarrhea (OR 0.23 [95% CI 0.28 to 0.65], p=0.006), nausea (OR 0.05 [95% CI 0.01 to 0.36], p=0.003), and bitter taste (OR 0.14 [95% CI 0.03 to 0.69], p=0.015). In addition, the probiotic group had lower gastrointestinal symptom rating scale (GSRS) scores (1.46 ± 0.36 vs. 2.65 ± 0.66, p<0.001) and higher SF-36 health-related quality-of-life scores (63.3 ± 10.2 vs. 57.3 ± 13.4, p=0.020) after treatment than the placebo group. Conclusion The probiotic adjuvant with 14-day standard triple therapy improved the H. pylori eradication rate. Supplementation with Lacidofil® STRONG during the 2-week eradication treatment and 4-week follow-up phase can help to reduce the gastrointestinal side effects of eradication therapy and increase patients’ general health-related quality of life.